2020
DOI: 10.3390/en13102489
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of School Building Energy Performance and Classroom Indoor Environment

Abstract: Existing building stock represents potential for energy saving renovations. Energy savings and indoor climate comfort are key demands for sustainable building refurbishment. Especially in schools, indoor comfort is an extremely important issue. A case study of energy consumption in selected school buildings in temperate climatic conditions of Central Europe region was performed. The studied buildings are representatives of various school premises constructed throughout the last century. The evaluation was base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Moreover, recalculation of results shown in Table 3 indicates that heat savings due to other measures analyzed were considered directly proportional to the expected heat savings by outer walls insulation, which is an oversimplification. Similarly, the expected electric energy savings due to lighting refit are evidently a rough estimate due to the lack of actual design and operation data [ 19 ] and findings acquirable by site visit only [ 13 , 20 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, recalculation of results shown in Table 3 indicates that heat savings due to other measures analyzed were considered directly proportional to the expected heat savings by outer walls insulation, which is an oversimplification. Similarly, the expected electric energy savings due to lighting refit are evidently a rough estimate due to the lack of actual design and operation data [ 19 ] and findings acquirable by site visit only [ 13 , 20 ].…”
Section: Resultsmentioning
confidence: 99%
“… Lighting refit is proposed. Given a probably wide range of existing lighting system quality, reliability, age, etc., such measure cannot be evaluated without a site visit [ 13 ]. Taking the building of our faculty as an example: the lighting is partly refitted, partly dysfunctional and there is no relevant information on how its operation time relates to working hours.…”
Section: General Commentsmentioning
confidence: 99%
“…They found that depending on the expected life cycle of the building, the priority of investments on more performing technologies should be accurately analyzed, being that not obvious. Mohelníková et al [24] analyzed several options for complex retrofits focused on building envelopes and their window/shading systems together with the installation of efficient technical systems for HVAC systems. Their analyses on heating energy demands in existing old buildings showed the importance of renovations for their energy efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…The classroom is the most important functional space in the teaching building and is also a staff-intensive space. The indoor comfort requirement is a basic requirement of the school and is more important than the energy conservation requirement [2]. The classroom should provide a comfortable and healthy indoor air environment because occupants may be in the classroom for a long time.…”
Section: Introductionmentioning
confidence: 99%